2018
DOI: 10.1177/0218492318755182
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery perforation complicating percutaneous coronary intervention

Abstract: Background Coronary artery perforation is a rare but serious complication of percutaneous coronary interventions. We aimed to evaluate the management of coronary artery perforation in Sulaimaniyah, Iraq. Methods A retrospective review of our medical records from 2009 to 2016 identified 24 patients (15 males, 9 females) with coronary artery perforation. Mean age was 60 ± 9.2 years (range 40-74 years). Standard diagnostic angiography or percutaneous interventions were performed. Coronary artery perforation was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Coronary artery perforation represents a rare, but potentially fatal complication surrounding PCI 5 with the most common etiology being guidewire manipulation into the extravascular space 6 . Management strategies for treating CAP must rely first upon hemodynamic stabilization 7 .…”
Section: Discussionmentioning
confidence: 99%
“…If unable to differentiate based on these parameters, a fourth investigator (PMik) would select between the papers with the article providing most data regarding our secondary objectives being selected for inclusion. Sixty-seven papers were included in the final statistical analysis4–7 10–72 (figure 1). Efforts to exclude data pertaining to CTO procedures within a larger dataset were made by the authors.…”
Section: Methodsmentioning
confidence: 99%